2017
DOI: 10.3390/su9061033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Government Policy and Drought from 1984 to 2009 on Rangeland in the Three Rivers Source Region of the Qinghai-Tibet Plateau

Abstract: Abstract:The Three Rivers Source Region of the Qinghai-Tibet Plateau is a key area that has extensive impacts on much of the population and economy of China as well as several Southeast Asian countries. The rangeland in this area has undergone degradation, the driving factors of which have been extensively investigated in previous studies. However, the effect of policy on rangeland was not analyzed by subdividing the study period according to the timing of the rangeland policies. The role of dry conditions dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This difference is probably due to the large differences in mean annual precipitation among sites (348 mm at the Tibetan site, 476 mm at the Qinghai site and 747 mm at our site). Lu et al (2017) suggested that precipitation of less than 400 mm during the growing season could limit the ANPP in the QTP alpine ecosystems. Thus, plant compensation induced by grazing may occur in regions where annual precipitation exceeds 400 mm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This difference is probably due to the large differences in mean annual precipitation among sites (348 mm at the Tibetan site, 476 mm at the Qinghai site and 747 mm at our site). Lu et al (2017) suggested that precipitation of less than 400 mm during the growing season could limit the ANPP in the QTP alpine ecosystems. Thus, plant compensation induced by grazing may occur in regions where annual precipitation exceeds 400 mm.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the dominant factors affecting resource availability in grassland ecosystems are precipitation, air temperature, nutrient availability, and soil water content (Frank et al, 2018). Previous studies have indicated that precipitation has a positive (Lezama et al, 2014; Lu et al, 2017) or neutral (Wang et al, 2012; Eldridge et al, 2016) effect on primary production in grasslands on a regional scale; in contrast, the timing of rainfall events and precipitation periods are key factors to affect ANPP on a plot scale (Knapp et al, 2012). Similarly, air temperature has a positive effect on ANPP (Wang et al, 2012; Lu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the lack of consideration of policy intervention impact on the landscape pattern, the future pattern prediction simulated by CA-Markov model obtained non-ideal performances under the ecological protection scenario. It is hard to quantify the effect of the policies [75][76][77], such as returning farmland to forestry, eco-migration policies [78], and check the coverage of all kinds of nature protection zones in space. Thus, the influence of policy intervention on landscape variation were not considered as a restriction factor.…”
Section: Discussionmentioning
confidence: 99%